Penegakan Hukum dan Penyelesaian Sengketa Peralihan Hak Atas Tanah Melalui Jual Beli Di Bawah Tangan - Aldhi Arrahman; Bagus Kurniawan; Ayu Faradilla; Muhammad Syahrul Rafli; Liga Alakbar (Sekolah Tinggi Ilmu Hukum Sumpah Pemuda, 2023)
The deal for the sale of land under that hand is still a problem because it does not provide legal certainty. Legal certainty occurs when laws are made and enacted in a clear and rational way. Norma does not raise doubt or obscurity, and it is also logical because it is a system of norms consisting of different norms so that they do not break or contradict each other. As a strong and legally valid proof of land ownership in accordance with the law, the land certificate is very important to the public. Proof of the sale of the land, giving an explanation of ownership. During the execution process, it's impossible to rename without the involvement of the Land Registry Officer.